The Main Receptors Involved in the COVID-19: A Systematic Review and Meta-Analysis - Câmara, Alice B.; Brandão, Igor Augusto (Current Medicinal Chemistry, 2021)
Objective: This review aims to study the receptor's family and functions most related to COVID-19 infection and also suggest the tissue and cell location on which the majority of COVID-19 receptors are mainly expressed. Methods: This systematic review is according to PRISMA guidelines. PubMed, Cochrane, SciELO, Lilacs, Web of Science, and DOAJ databases were used. Clinical trials and research articles studying receptors related to COVID-19 were included in this review. R programming language was used to elaborate charts and receptors network, and SPSS(26v) software was used to perform statistical analysis (PROSPERO: CRD42020210643). Results: The majority of studies on the involvement of receptors in COVID-19 included plasma receptors and G protein-coupled receptor families (p<0.05). These receptors are highly expressed in the brain (24%) and 80% of them can interact with each other in a protein network, exerting some regulatory effects on various tissues. The main influential receptor in the network of receptors involved in the COVID-19 was the EGFR and the majority of receptors were associated with pathological processes of the disease (p<0.05), including the amplification of inflammatory responses in COVID-19, which may be related to neurological disorders in some cases. Studies on receptors involved in the COVID-19 included mainly patients from the United States, Spain, and Brazil (p<0.05). Conclusion: Plasma receptors and G protein-coupled receptors, especially the EGFR, involved in pathological effects of the COVID-19 inflammatory process in the brain have shown significant importance in this review.
Keywords: G protein-coupled receptor